أثر انخفاض أسعار النفط عالمياً على نمو الناتج المحلي الإجمالي في العراق - كاظم، رؤى محمد (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2018)
السلوك التاريخي لتحركات أسعار النفط ومساهمة النفط في تحصيل العملات الصعبة وتأثير انخفاض أسعار النفط على النمو الناتج المحلي الإجمالي في العراق، ينطلق البحث من فرضية أساسية مفادها أن استمرار هيمنة الإيرادات النفطية على الإيرادات العامة للدولة سيؤدي إلى انعكاسات سلبية خطيرة على النمو الاقتصادي في العراق بسبب التذبذب المستمر لأسعار النفط الخام في السوق العالمي لأسباب اقتصادية وسياسية دولية ولتحقيق هدف وفرضية البحث فقد قسم إلى ثلاثة أجزاء، تضمن الجزء الأول السلوك التاريخي لتحركات أسعار النفط، أما الجزء الثاني فقد جاء بعنوان مساهمة النفط في تحصيل العملات الصعبة، وكذلك الجزء الثالث تحليل أثر انخفاض أسعار النفط على نمو الناتج المحلي الإجمالي، وأخيرا انتهي البحث إلى جملة من النتائج والتوصيات.
The research tackles the impact of global oil prices on GDP growth in Iraq. It aims at knowing the historical behavior of the movements of oil prices. the contribution of oil to the collection of foreign currencies and the impact of the decline in oil prices on the growth of the gross domestic product in Iraq. The continued dominance of oil revenues over the public revenues of the state will lead to serious negative repercussions on economic growth in Iraq due to the continuous fluctuation of crude oil prices in the global market for economic and political reasons. In order to achieve the objective and hypothesis of the research. The first part included the historical behavior of the movements of oil prices. The second part was entitled "The contribution of oil to the collection of hard currency." The third part analyzes the impact of the decline in oil prices on GDP growth. Finally. The research concluded with a number of conclusions and recommendations.
Keywords: النفط -- أسعار النفط -- الناتج المحلي الإجمالي -- النمو الاقتصادي -- الاقتصاد العراقي